Jujitsu terminology : Japanese jujitsu martial arts terminology English to Japanese & Japanese to English translations - Hill, Tom. ([Luton, England] : Andrews UK Limited, 2014)
Most of the Jujitsu terminology any student of the Japanese Martial Arts will ever need. In Japanese to English and English to Japanese. By Tom Hill; 40 years Martial Arts experience, 3rd Dan BKA (British Karate Association), 4th Dan Academy of Goju Ryu, 6th Dan Shotokan; Jin Sei Kai, 8th Dan Goju.co.uk & Chief instructor, Special Advisor to; Combat Jujitsu Hellas.
Cover; Contents; Front Matter; Title Page; Publisher Information; Jujitsu Terminology; Japanese Pronunciation; English to Japanese; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; X; Y; Z; Japanese to English; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; X; Y; Z; Counting; Martial Arts Rank Or Grading System; Black Belt Ranks; Kyu Grades; Author's Note; Back Matter; Also Available.
"Most of the terminology any student of Jujitsu the Japanese Martial Art will ever need."--Cover.
Online resource; title from PDF cover (ebrary, viewed March 12, 2014).
eBooks on EBSCOhost
Keywords: Jiu-jitsu -- Languages; Jiu-jitsu -- Training; Hand-to-hand fighting, Oriental; Mixed martial arts; Martial arts; Jiu-jitsu -- Langues; Arts martiaux; Arts martiaux mixtes; martial arts; GAMES -- Gambling -- Sports; SPORTS & RECREATION -- Business Aspects; SPORTS & RECREATION -- Essays; SPORTS & RECREATION -- History; SPORTS & RECREATION -- Reference; TRAVEL -- Special Interest -- Sports; Martial arts; Hand-to-hand fighting, Oriental; Jiu-jitsu -- Training; Mixed martial arts